COMPARING THE PHONOLOGICAL SYSTEM OF MANIKLIYU DIALECT AND THAT OF SUTER DIALECT OF THE BALINESE LANGUAGE: A DESCRIPTIVE STUDY - ., I Dewa Made Yuda Mahendra; ., Prof. Dr.I Ketut Seken,MA; ., Drs. I Wayan Suarnajaya,MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk mendeskripsikan membandingkan sistem fonologis Manikliyu Dialek dan Suter Dialek bahasa Bali: penelitian deskriptif, yang meliputi jenis vokal yang digunakan dalam Manikliyu Dialek dan Suter Dialek dari Bali, jenis konsonan digunakan dalam Manikliyu Dialek dan Suter Dialek Bali dan perbedaan dalam hal pengucapan kata antara Manikliyu dialek dan Suter dialek dari Bali. Penelitian ini merupakan penelitian deskriptif kualitatif. Ada tiga informan utama dan beberapa informan sekunder dalam penelitian ini. Data yang diperoleh dikumpulkan berdasarkan tiga teknik, yaitu observasi, wordlist, dan panduan wawancara. Hasil analisis data menunjukkan bahwa ada 10 jenis vokal di Manikliyu Dialek, ada 8 jenis vokal di Suter Dialek, ada 19 jenis konsonan di Manikliyu dialek, ada 19 jenis konsonan di Suter Dialek dan ada 62 jenis kata memiliki pengucapan perbedaan dalam hal vokal dan konsonan mereka antara Manikliyu dan Suter Dialek.Kata Kunci : fonologi, vokal, konsonan, perbedaan dalam hal pengucapan kata antara Manikliyu Dialek dan Suter Dialek dari Bali. This study aimed at describing comparing the phonological system of Manikliyu Dialect and Suter Dialect of Balinese language: a descriptive study, which covered the types of vowels used in Manikliyu Dialect and Suter Dialect of Balinese, the types of consonants used in Manikliyu Dialect and Suter Dialect of Balinese and the differences in terms of word pronunciation between Manikliyu Dialect and Suter Dialects of Balinese. This research is a descriptive qualitative research. There were three main informants and several secondary informants in this research. The obtained data were collected based on three techniques, namely observation, wordlist, and interview guide. The results of the data analysis show that there are 10 types of vowels in Manikliyu Dialect, there are 8 types of vowels in Suter Dialect, there are 19 types of consonants in Manikliyu dialect, there are 19 types of consonant in Suter Dialect and there are 62 kinds of words have a differences pronunciation in terms of their vowels and consonants between Manikliyu and Suter Dialects. keyword : phonology, vowel, consonant, differences in terms of word pronunciation between Manikliyu Dialect and Suter Dialects of Balinese.